Employer Branding: An Islamic Perspective - Ibrahim, Norasyikin binti Shaikh (UI Scholars Hub, 2016)
This paper discusses employer branding from an Islamic perspective. Islam is a way of life and so do the employer and employee relationship, which strengthens employer branding in an organization. The definition, importance and process related to employer branding are discussed in the context of human resource management, such as job satisfaction and work environment. In addition to that, related human resource management practices such as recruitment and selection were discussed in an Islamic context. Related concepts such as employee value proposition (EVP), ethics and Islamic values were discussed with reference from Al-Quran and Hadith. The paper concludes with a few suggestions and recommendations on instilling Islamic values for effective employer branding.